Organic anion transporter 5 renal expression and urinary excretion in rats with vascular calcification - Hazelhoff, Maria Herminia (2013)
It has been described renal damage in rats with vascular calcification. The organic anion transporter 5 (Oat5) is only expressed in kidney, and its urinary excretion was proposed as potential early biomarker of renal injury. The aim of this study was to evaluate the Oat5 renal expression and its urinary excretion in an experimental model of vascular calcification in comparison with traditional markers of renal injury. Vascular calcification was obtained by the administration of an overdose of vitamin D3 (300,000 IU/kg, b.w., i.m.) to male Wistar rats. Oat5 urinary abundance was evaluated by Western blotting. Traditional markers of renal injury, such as creatinine and urea plasma levels, urinary protein levels, and urinary alkaline phosphatase (AP) activity, were determined using commercial kits. Histology was assessed by hematoxylin/eosin staining. Oat5 renal expression was evaluated by Western blotting and by immunohistochemistry. An increased expression of Oat5 in renal homogenates, in apical membranes, and in its urinary excretion was observed in rats with vascular calcification. The traditional parameters used to evaluate renal function were not modified, with the exception of histology. It is possible to postulate the urinary excretion of Oat5 as a potential noninvasive biomarker of renal injury associated with vascular calcification.